2006
DOI: 10.1021/bc050322y
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Function Engineering of Interferon-β-1b for Improving Stability, Solubility, Potency, Immunogenicity, and Pharmacokinetic Properties by Site-Selective Mono-PEGylation

Abstract: Recombinant interferon-beta-1b (IFN-beta-1b) is used clinically in the treatment of multiple sclerosis. In common with many biological ligands, IFN-beta-1b exhibits a relatively short serum half-life, and bioavailability may be further diminished by neutralizing antibodies. While PEGylation is an approach commonly employed to increase the blood residency time of protein therapeutics, there is a further requisite for molecular engineering approaches to also address the stability, solubility, aggregation, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(153 citation statements)
references
References 55 publications
3
146
0
1
Order By: Relevance
“…Significantly improved physico-chemical characteristics after coupling of PEG to a protein can be explained by the increased hydrodynamic volume of the PEG-protein conjugate resulting from the ability of PEG to coordinate water molecules and from the high flexibility of the PEG chain. Consequently, apparent Mw of the PEG-protein conjugate is around 5 to 10 fold higher in comparison to the globular protein of the same nominal Mw [26]. PEG chains can sweep around the protein to shield and protect it from the environment (or vice versa), but they also influence the interactions of the protein that are responsible for its biological function.…”
mentioning
confidence: 99%
“…Significantly improved physico-chemical characteristics after coupling of PEG to a protein can be explained by the increased hydrodynamic volume of the PEG-protein conjugate resulting from the ability of PEG to coordinate water molecules and from the high flexibility of the PEG chain. Consequently, apparent Mw of the PEG-protein conjugate is around 5 to 10 fold higher in comparison to the globular protein of the same nominal Mw [26]. PEG chains can sweep around the protein to shield and protect it from the environment (or vice versa), but they also influence the interactions of the protein that are responsible for its biological function.…”
mentioning
confidence: 99%
“…Modification of lysine or cysteine residues of proteins with poly(ethylene glycol) (PEG), generally known as PEGylation, is the most widely used polymer conjugation approach to improve the pharmacological profiles of proteins, and several PEGylated proteins are used clinically as therapeutics (2)(3)(4)(5). Unfortunately, most proteins contain numerous chemically reactive residues that are promiscuously distributed on their surface, which can result in the formation of heterogeneous protein-polymer conjugates with unacceptably low biological activity (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…For instance, recent studies reported that covalent attachments of poly(ethylene) glycol to the surfaces of acetylcholinesterase or interferon-β-1b have shown a meaningful increase in the circulatory residency times [5,6]. Similarly, conjugation of poly(ethylene) glycol with hemoglobin has been suggested to act a hemoglobin-based oxygen carrier.…”
Section: Conjugated Haemoglobinmentioning
confidence: 99%